2020
DOI: 10.1007/s10067-020-05421-9
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making in gout treatment: a national study of rheumatology provider opinion and practice

Abstract: Author contributions: Jasvinder A. Singh designed the study, developed study protocol, performed and reviewed analyses and wrote the first draft of the paper. Drs. Barton and Ms. Toupin-April provided comments on the study survey. All authors reviewed analyses, revised the manuscript, read, and approved the final manuscript. Declarations:Ethics/IRB approval and consent to participate: This was a QI initiative that only assessed opinions of healthcare providers and therefore an Institutional Review Board (IRB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A study in the USA on rheumatologists’ views and practices related to SDM in gout treatment revealed that 70% of the rheumatologists reported to offer patients offering a choice whether or not to start ULT without a DA. 44 Our DA might support patients and physicians in this shared decision.…”
Section: Discussionmentioning
confidence: 92%
“…A study in the USA on rheumatologists’ views and practices related to SDM in gout treatment revealed that 70% of the rheumatologists reported to offer patients offering a choice whether or not to start ULT without a DA. 44 Our DA might support patients and physicians in this shared decision.…”
Section: Discussionmentioning
confidence: 92%
“…31 In addition to addressing bone-related problems, rheumatologists are progressively inclined to engage in discussions pertaining to aspects beyond the direct pharmacological management of joint ailments, including patient quality of life and education. 34,35 The implementation of improved pharmacy services has been recognized as a means to effectively tackle issues pertaining to medications and drug-related concerns. The involvement of pharmacists in primary health care should be further elucidated in the management of patients with gout, particularly with regard to the current provision of patient education and the monitoring of medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to addressing bone‐related problems, rheumatologists are progressively inclined to engage in discussions pertaining to aspects beyond the direct pharmacological management of joint ailments, including patient quality of life and education 34,35 . The implementation of improved pharmacy services has been recognized as a means to effectively tackle issues pertaining to medications and drug‐related concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision-making remains a topic ill studied in rheumatology, and tools to support physicians and patients in this process are lacking [ 4 ]. In a survey on gout treatment, rheumatologists indicated that no treatment choice was offered to the patient, and if patients could make choices, they often had difficulty making them [ 5 ]. The lack of patient knowledge on topics related to treatment options was perceived as a main barrier.…”
mentioning
confidence: 99%